Adjuvant treatment for patients with FIGO stage I uterine serous carcinoma confined to the endometrium. Issue 8 (August 2020) - Nasioudis, Dimitrios; Roy, Allison Grace; Ko, Emily M; Cory, Lori; Giuntoli, Robert L; Haggerty, Ashley F; Kim, Sarah H; Morgan, Mark A; Latif, Nawar A
ABSTRACT : Objectives : The role of adjuvant treatment for early‐stage uterine serous carcinoma is not defined. The goal of this study was to investigate the impact of adjuvant treatment on survival of patients with tumors confined to the endometrium. Methods : Patients diagnosed with stage I uterine serous carcinoma with no myometrial invasion between January 2004 and December 2015 who underwent hysterectomy with at least 10 lymph nodes removed were identified from the National Cancer Database. Adjuvant treatment patterns defined as receipt of chemotherapy and/or radiotherapy within 6 months from surgery were investigated and overall survival was evaluated using Kaplan‐Meier curves, and compared with the log‐rank test for patients with at least one month of follow‐up. A Cox analysis was performed to control for confounders. Results : A total of 1709 patients were identified; 833 (48.7%) did not receive adjuvant treatment, 348 (20.4%) received both chemotherapy and radiotherapy, 353 (20.7%) received chemotherapy only, and 175 (10.2%) received radiotherapy only. Five‐year overall survival rates for patients who did not receive adjuvant treatment (n=736) was 81.9%, compared with 91.3% for those who had chemoradiation (n=293), 85.1% for those who received radiotherapy only (n=143), and 91.0% for those who received chemotherapy only (n=298) (p<0.001). After controlling for age, insurance status, type of treatment facility, tumor size, co‐morbidities, and history of another tumor, patients who received adjuvant chemotherapy (HR 0.64, 95% CI 0.42, 0.96), or chemoradiation (HR 0.55, 95% CI 0.35, 0.88) had better survival compared with those who did not receive any adjuvant treatment, while there was no benefit from radiotherapy alone (HR 0.85, 95% CI 0.53, 1.37). There was no survival difference between chemoradiation and chemotherapy only (HR 1.15, 95% CI 0.65, 2.01). Conclusion : Adjuvant chemotherapy (with or without radiotherapy) is associated with a survival benefit for uterine serous carcinoma confined to the endometrium.